WACANA PENAMBAHAN KEWENANGAN DEWAN PERWAKILAN DAERAH SEBAGAI LEMBAGA LEGISLATIF - Aldani, Abin Rifa (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2023)
Since the amendment to the 1945 Constitution of the Republic of Indonesia which has been running for 20 years, the role and authority of the Regional Representative Council (DPD) is very limited. Based on its basic authority as in article 22D, the DPD is equipped with the authority to propose bills, discuss bills, and carry out supervision which is used as a consideration by the DPR on products and the implementation of laws relating to regionalism. Seeing the condition and influence of the DPD which is not very significant, the discourse to strengthen or dissolve the DPD in the Indonesian constitutional system cannot fail to be an important factor that cannot be separated from amending and revising its derivative regulations. Departing from this, the proposal to strengthen the DPD could have implications for implementing the concept of